The role of neuroinflammation and neurovascular dysfunction in major depressive disorder - Jeon SW (Dove Medical Press, 2018)
Sang Won Jeon,1 Yong-Ku Kim2 1Department of Psychiatry, Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, Seoul, 2Department of Psychiatry, Korea University Ansan Hospital, Korea University College of Medicine, Ansan, South Korea Abstract: Although depression has generally been explained with monoamine theory, it is far more multifactorial, and therapies that address the disease’s pathway have not been developed. In this context, an understanding of neuroinflammation and neurovascular dysfunction would enable a more comprehensive approach to depression. Inflammation is in a sense a type of allostatic load involving the immune, endocrine, and nervous systems. Neuroinflammation is involved in the pathophysiology of depression by increasing proinflammatory cytokines, activating the hypothalamus–pituitary–adrenal axis, increasing glucocorticoid resistance, and affecting serotonin synthesis and metabolism, neuronal apoptosis and neurogenesis, and neuroplasticity. In future, identifying the subtypes of depression with increased vulnerability to inflammation and testing the effects of inflammatory modulating agents in these patient groups through clinical trials will lead to more concrete conclusions on the matter. The vascular depression hypothesis is supported by evidence for the association between vascular disease and late-onset depression and between ischemic brain lesions and distinctive depressive symptoms. Vascular depression may be the entity most suitable for studies of the mechanisms of depression. Pharmacotherapies used in the prevention and treatment of cerebrovascular disease may help prevent vascular depression. In future, developments in structural and functional imaging, electrophysiology, chronobiology, and genetics will reveal the association between depression and brain lesions. This article aims to give a general review of the existing issues examined in the literature pertaining to depression-related neuroinflammatory and vascular functions, related pathophysiology, applicability to depression treatment, and directions for future research. Keywords: depressive disorder, neuroinflammation, psychoneuroimmunology, vascular depression, vascular disease